A study of some enzymes of glycerolipid biosynthesis in rat liver after subtotal hepatectomy - Mangiapane, E. Heather (1973)
1. The accumulation of triglyceride in the liver remnant after subtotal hepatectomy (removal of 82% of the liver) exceeded that described for partial hepatectomy (removal of 70% of the liver). 2. Palmitoyl-CoA synthetase, glycerol phosphate acyltransferase and diglyceride acyltransferase activities were measured in the microsomal fraction, and phosphatidate phosphohydrolase activity was measured in the particle-free supernatant fraction, prepared from the liver remnant at various times after subtotal hepatectomy. 3. The only enzyme showing a significant change in specific activity was phosphatidate phosphohydrolase. The specific activity was approximately fivefold that of the control value at 6h after operation and threefold that of the control at 10, 16 and 24h after operation. A smaller increase in the specific activity of the enzyme in sham-operated animals occurred only at 6h after operation. 4. However, at this time the total phosphohydrolase activity of the remaining liver in the sham-operated rats was approximately threefold that in hepatectomized rats. 5. Injection of actinomycin D prevented the increase in activity of phosphatidate phosphohydrolase but did not prevent the accumulation of triglyceride.